The impact of the crisis on employment and the role of labour market institutions - Werner Eichhorst; Verónica Escudero; Paul Marx; Steven Tobin (Institute for the Study of Labor (IZA), 2010)
The paper takes a comparative perspective on the labour market impact on G20 and EU countries of the financial and economic crisis that began in 2008. It starts from the observation that the decline in employment and rise in unemployment in relation to output or GDP reductions varies significantly across countries. It examines the impacts from an institutional perspective taking into account different channels of external, internal and wage flexibility determined by both the institutional arrangements in place before the crisis and discretionary reforms implemented during the crisis. Emphasis is placed on the role of permanent and temporary jobs, working time adjustment, wage flexibility and active and passive labour market policies. The paper shows that, at least for the time being, unemployment increases have been contained in countries with comparatively strong internal flexibility. At the same time, however, it appears that the crisis has - at least in some cases - contributed to a further dualization of labour markets given that risks are allocated unequally across types of employment.
Keywords: J58; J65; J21; 330; crisis; employment; EPL; institutions; flexibility; dual labour markets